Process as theory in information systems research - Kevin Crowston (Proceedings of the IFIP TC8 WG8. 2 International Working Conference on the Social and Organizational Perspective on Research and Practice in Information Technology, 2000)
Many researchers have searched for evidence of organizational improvements from the huge sums invested in ICT. Unfortunately, evidence for such a pay back is spotty at best (e.g., Brynjolfsson 1994; Brynjolfsson and Hitt 1998; Meyer and Gupta 1994). On the other hand, at the individual level, computing and communication technologies are increasingly merging into work in ways that make it impossible to separate the two (e.g., Bridges 1995; Gasser 1986; Zuboff 198). This problem—usually referred to as the productivity paradox—is an example of a more pervasive issue: linking phenomena and theories from different levels of analysis. Organizational processes provide a bridge between individual, organizational, and even industrial level impacts of information and communication technologies (ICT). Viewing a process as the way organizations accomplish desired goals and transform inputs into outputs makes the link to organizational outcomes. Viewing processes as ordered collections of activities makes the link to individual work, since individual actors perform these activities. As well, process theories can be a useful milieu for theoretical interplay between interpretive and positivist research paradigms. A process-centered research framework is illustrated with an analysis of the process of seating and serving customers in two restaurants. The analysis illustrates how changes in individual work affect the process and thus the organizational outcomes and how processes provide a theoretical bridge between work at different levels of analysis.
Reprinted in Malone, T. W., Crowston, K. & Herman, G. (Eds.) Organizing Business Knowledge: The MIT Process Handbook (pp. 177–190). Cambridge, MA: MIT Press, 2003.
Keywords: Process